General and selective deoxygenation by hydrogen using a reusable earth-abundant metal catalyst - Schwob, T.; Kunnas, P.; De Jonge, Niels; Papp, Christian; Steinrück, Hans-Peter; Kempe, Rhett (Science Advances, 2019)
Chemoselective deoxygenation by hydrogen is particularly challenging but crucial for an efficient late-stage modification of functionality-laden fine chemicals, natural products, or pharmaceuticals and the economic upgrading of biomass-derived molecules into fuels and chemicals. We report here on a reusable earth-abundant metal catalyst that permits highly chemoselective deoxygenation using inexpensive hydrogen gas. Primary, secondary, and tertiary alcohols as well as alkyl and aryl ketones and aldehydes can be selectively deoxygenated, even when part of complex natural products, pharmaceuticals, or biomass-derived platform molecules. The catalyst tolerates many functional groups including hydrogenation-sensitive examples. It is efficient, easy to handle, and conveniently synthesized from a specific bimetallic coordination compound and commercially available charcoal. Selective, sustainable, and cost-efficient deoxygenation under industrially viable conditions seems feasible.
CRIS-Team Scopus Importer:2021-04-20